2018
DOI: 10.1007/s10549-018-4663-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly favorable physiological responses to concurrent resistance and high-intensity interval training during chemotherapy: the OptiTrain breast cancer trial

Abstract: BackgroundAdvanced therapeutic strategies are often accompanied by significant adverse effects, which warrant equally progressive countermeasures. Physical exercise has proven an effective intervention to improve physical function and reduce fatigue in patients undergoing chemotherapy. Effects of high-intensity interval training (HIIT) in this population are not well established although HIIT has proven effective in other clinical populations. The aim of the OptiTrain trial was to examine the effects of concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
132
4
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(168 citation statements)
references
References 36 publications
(58 reference statements)
8
132
4
24
Order By: Relevance
“…An additional limitation is that the current approach does not allow for separating the effects of anthracyclines from those of taxanes. However, a subgroup analysis in the general trial showed similar effects on muscle strength and cardiorespiratory fitness regardless of chemotherapy regimen (18). The low attendance rate in the RT-HIIT group may have underestimated the potential effects of an RT-HIIT regimen in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…An additional limitation is that the current approach does not allow for separating the effects of anthracyclines from those of taxanes. However, a subgroup analysis in the general trial showed similar effects on muscle strength and cardiorespiratory fitness regardless of chemotherapy regimen (18). The low attendance rate in the RT-HIIT group may have underestimated the potential effects of an RT-HIIT regimen in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Exercise session attendance was calculated as the mean of the individual percentages (attended exercise sessions divided by the total number of sessions). Muscle strength was measured by isometric midthigh pull as described previously (18). Cancer-related fatigue was selfassessed at baseline and at 16 wk using the EORTC QLQ-C30 questionnaire (version 3.0) (31).…”
Section: Other Measuresmentioning
confidence: 99%
See 3 more Smart Citations